Analisis Kontrastif Perspektif Bahasa dan Budaya terhadap Distingsi Gender Maskulin Versus Feminin dalam Bahasa Arab dan Bahasa Indonesia - Tajudin Nur (Humaniora, 2011)
This paper discusses the reflection of gender in Arabic and Indonesian languages and then connects it to their each cultural contexts. Gender in Arabic grammar is important subcategory that distinguishes between masculine and feminine in almost every part of speech, whereas gender in Indonesian is not an important subcategory. After data analysis through comparison and elaboration phases obtained the following results: (1) the gender markers in Arabic are dominated by the grammatical markers, while the gender markers in Indonesian are dominated by the lexical markers and if it not significant the gender markers in Indonesian are not presented, and (2) Arabic strictly applies the gender system and is closely related to the rules of concord (agreement), while Indonesian loosely does it and does not own the rules of conformity. The distinction of gender system between the two languages shows the different of cultural system also. Based on social structure system, the Arab society emphasizes the gender segregation like man versus woman, while the society of Indonesia emphasizes the age and status distinctions. Based on genetic relationship system, the Arab people tend to be individual, while the Indonesian people tend to have mutual cooperation and collectiveness. Based on cultural system, the Arab people applying strict patriarchy, while the Indonesian people applying loose patriarchy.